Home (bayit) and Bread (lechem): Masculine Power and Female Authority in the Book of Ruth - Cohen, Tzachi (Women in Judaism, 2022)
A deep look at the Book of Ruth reveals a two-dimensional model that reflects two alternative realities of gender. One perception strives to manage the world and resolve its problems. It is an orientation based on justice, rules, and individualistic logic, and even a certain degree of manipulation. The other exists within human reality and is based on concern for others, sensitivity, and mutual responsibility. Although these perceptions are obviously not necessarily representative of different genders, they are often associated as such and can be referred to as masculine and feminine, respectively. This paper demonstrates how the story of Ruth in its entirety revolves around the tension between these two perceptions, until they ultimately merge into one.